Time is of the essence - Heaney, M (1997)
The issue of time underlies much of the discussion about the relationships between Work, Expression, Manifestation and Item (to use the terms applied in Functional Requirements of Bibliographic Records), and is at the root of many of the difficulties associated with online publications, but it is much neglected. So far, only the paper on serials raises it as a substantive issue; the fact that it permeates many of our decisions on every area of cataloguing is obscured by the acceptance of unspoken presumptions. Functional Requirements of Bibliographic Records largely ignores the time aspect,but I suggest there is much to be gained from an analysis, at each level (Work, Expression, Manifestation, Item) of: (a) how objects/entities of library interest exist over time; (b) how or whether they change over time (c) how or whether their existence is reflected in some sort of physical reality, tangible or not (d) whether the physical reality is continuous or intermittent.